Analisis Faktor-Faktor Yang Mempengaruhi Kemiskinan Di Aceh Bagian Timur - Farid Alfasyah; Muhammad Fadhel Alfayed; Liansyah Pratama; Asnidar Asnidar; Ahmad Ridha (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
poverty is an important indicator to see the increase and decrease in Economic Growth, Population Growth, and also Inflation in eastern Aceh including Aceh Tamiang, East Aceh, Langsa. The purpose of this study is to see or analyze economic growth, population growth, and inflation in eastern Aceh for the 2011-2020 period. This study uses multiple linear regression analysis methods. The data processing tool used is Eviews 12. The approach used in this research is a quantitative approach. The data used in this study is secondary data and is a form of time series data. The approach used in this research is a quantitative approach. The results of data analysis in the study showed that economic growth had a positive and significant effect on poverty in eastern Aceh, population growth had a negative and significant effect on poverty in eastern Aceh, and inflation had a negative and insignificant effect on poverty in eastern Aceh. And the F test (simultaneous) shows that Economic Growth, Population Growth, and Inflation have a significant effect on poverty.